Activity-related typologies and longitudinal change in physical activity and sedentary time in children and adolescents: The UP&DOWN Study - Kate Parker; Anna Timperio; Jo Salmon; Karen Villanueva; Helen Brown; Irene Esteban-Cornejo; Veronica Cabanas-Sánchez; José Castro-Piñero; David Sánchez-Oliva; Oscar L. Veiga (Journal of Sport and Health Science, 2021)
Background: Children and adolescents can be distinguished by different typologies (clusters) of physical activity and sedentary behavior. How physical activity and sedentary behaviors change over time within different typologies is not known. This study examined longitudinal changes in physical activity and sedentary time among children and adolescents with different baseline typologies of activity-related behavior. Methods: In this longitudinal study (3 annual time points) of children (n = 600, age = 9.2 ± 0.4 years (mean ± SD), 50.3% girls) and adolescents (n = 1037, age = 13.6 ± 1.7 years, 48.4% girls), participants were recruited in Spain in 2011–2012. Latent class analyses identified typologies based on self-reported screen, educational, social and relaxing sedentary behaviors, active travel, muscle strengthening activity, and sport at baseline. Within each typology, linear mixed growth models explored longitudinal changes in accelerometer-derived moderate-to-vigorous physical activity and sedentary time, as well as time by class interactions. Results: Three typologies were identified among children (“social screenies”, 12.8%; “exercisers”, 61.5%; and “non-sporty active commuters”, 25.7%) and among adolescents (“active screenies”, 43.5%; “active academics”, 35.0%; and “non-sporty active commuters”, 21.5%) at baseline. Sedentary time increased within each typology among children and adolescents, with no significant differences between typologies. No changes in physical activity were found in any typology among children. In adolescents, physical activity declined within all typologies, with “non-sporty active commuters” declining significantly more than “active screenies” over 3 years. Conclusion: These results support the need for intervention to promote physical activity and prevent increases in sedentary time during childhood and adolescence. Adolescents characterized as “non-sporty active commuters” may require specific interventions to maintain their physical activity over time.